2019
DOI: 10.3390/life9020040
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Homocysteine Thiolactone in A Prebiotic Perspective

Abstract: Homocysteine is a non-proteinogenic sulfur-containing amino acid. Like cysteine, it can form disulfide bridges and complex metallic cations. It is also closely related to methionine, the first amino acid in the synthesis of all contemporary proteins. Furthermore, its cyclized form, a five-membered ring thiolactone, is stable in acidic and neutral water. Here, we demonstrate that this thiolactone may have been formed in the primitive ocean directly from the Strecker precursor of homocysteine, an aminonitrile. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Homocysteine has a -SH group like thiols (RSH) and this group is susceptible to oxidation in the presence of metal catalysts and molecular oxygen [22]. Moreover, homocysteine can also form Hcy-thiolactone, exacerbating oxidative stress, and it can produce hydrogen peroxide [23,24]. A high homocysteine production reduces hydrogen sulfide (H 2 S), and imbalance between homocysteine and H 2 S increases oxidative stress [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Homocysteine has a -SH group like thiols (RSH) and this group is susceptible to oxidation in the presence of metal catalysts and molecular oxygen [22]. Moreover, homocysteine can also form Hcy-thiolactone, exacerbating oxidative stress, and it can produce hydrogen peroxide [23,24]. A high homocysteine production reduces hydrogen sulfide (H 2 S), and imbalance between homocysteine and H 2 S increases oxidative stress [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…91,167 Thus, de Duve proposed a "Thioester World" period during the transition from prebiotic chemistry to biochemistry, which was later explored by others. 114,[168][169][170][171][172] The plausibility of an ancient, thioester-dependent metabolism was recently reinforced by a computational analysis of thermodynamic properties and topologies of all known metabolic transformations. Using network expansion algorithms, Segrè and co-workers obtained a hypothetical metabolic network resembling a primitive (r)TCA cycle, that serves as a hub for the synthesis of acetyl, malonyl, malyl and succinyl thioesters.…”
Section: Prebiotic Thioester Chemistry In the Context Of Bioenergeticsmentioning
confidence: 99%
“…33 If this is the case, the aminonitrile 14 should be an intermediate; 14 has been synthesized (in a non-prebiotic manner), and it has been shown that its first evolution product in water is not homocysteine itself but its thiolactone 15. 39 It is therefore possible that this thiolactone existed on a primitive Earth rich in cyanides. It is fairly stable in water, although it eventually hydrolyzes to homocysteine (faster in basic water, of course), and could have participate in a de°Duve's thioester world.…”
Section: Homocysteine and Its Thiolactonementioning
confidence: 99%
“…50 However, as the chemistry of methionine makes it difficult to explain this, 51,52 it could in fact be that the first starting amino acid was rather homocysteine (or one of its derivatives) which via its thiolactone could have aminoacylated any pre-existing peptide chain in the N-terminal position. 39 Otherwise, Met residues are sometimes used to complex metal cations (but much less often than Cys). 53,54 They are involved in redox processes (forming the corresponding sulfoxide) 55 and frequently participate in the stabilization of protein structure thanks to the interaction of their sulfur atom with aromatic groups.…”
Section: Short Review Synthesismentioning
confidence: 99%